2021
DOI: 10.3390/diseases9040080
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility, Biofilm Production, and Detection of mecA Gene among Staphylococcus aureus Isolates from Different Clinical Specimens

Abstract: The increasing incidence of methicillin-resistant and biofilm-forming S. aureus isolates in hospital settings is a gruesome concern today. The main objectives of this study were to determine the burden of S. aureus in clinical samples, assess their antibiotic susceptibility pattern and detect biofilm formation and mecA gene in them. A total of 1968 different clinical specimens were processed to isolate S. aureus following standard microbiological procedures. Antibiotic susceptibility test of the isolates was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
(57 reference statements)
3
17
0
Order By: Relevance
“…Gaire et al, reported that most isolates susceptible to ciprofloxacin, gentamycin, clindamycin and cefoxitin were weak biofilm producers. In contrast, in the same study, it was reported that most isolates resistant to penicillin and erythromycin produced weak biofilms [ 66 ]. In contrast to our results, Sun et al, showed that isolates resistant to tetracycline were stronger biofilm producers than susceptible isolates [ 67 ].…”
Section: Discussionmentioning
confidence: 96%
“…Gaire et al, reported that most isolates susceptible to ciprofloxacin, gentamycin, clindamycin and cefoxitin were weak biofilm producers. In contrast, in the same study, it was reported that most isolates resistant to penicillin and erythromycin produced weak biofilms [ 66 ]. In contrast to our results, Sun et al, showed that isolates resistant to tetracycline were stronger biofilm producers than susceptible isolates [ 67 ].…”
Section: Discussionmentioning
confidence: 96%
“…Multidrug resistant S.aureus was found to be present in 85.5% of the cases. This is in contrast to the 44% stated by [24]. Antibiotic usage is driving the evolution of resistance [25].…”
Section: Discussionmentioning
confidence: 77%
“…As a result, the greater prevalence of MDR could be attributable to antibiotic overuse and abuse, which is frequent in Sokoto, Nigeria. Many phenotypic methods to detect MRSA have been developed but they are slow and vary in sensitivity and specificity [27] [24] (Gaire et al 2021) in which 36.5% and 53% were mecA positive respectively. Our result is lower compared to a report by [30] Hadyeh et al 2019, [31] McTavish et al 2019 who reported 95% mecA positive.…”
Section: Discussionmentioning
confidence: 99%
“…They were sown in Mueller-Hinton and Columbia culture medium (Bio-Merieux, Craponne, France). The bacterial suspension used corresponded to a concentration of 10 7 colonies per training unit/mL micro-test, which correspond to a turbidity of the 0.5 Mac Farland tube (Figures 5 and 6) [30]. The Kirby-Bauer test for antibiotic susceptibility, known as the disc diffusion test, is a standard that has been used for years.…”
Section: • Antibacterial Effect Testing Technique Of the Vegetable Ex...mentioning
confidence: 99%